2021
DOI: 10.21203/rs.3.rs-215681/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carboplatin-induced Senescence in Ovarian Cancer Cells Is Reversed Through EGFR and NF-κB Signaling

Abstract: Background: Metastases and recurrence of ovarian cancer after surgery and chemotherapy account for most cancer-related deaths, yet the mechanism underlying metastases and recurrence remains poorly understood. Recent evidence demonstrates that although long-lasting cells were considered tumor suppressors, senescent cancer cells, can induce the metastases and recurrence. In this study, we focused on the fate of ovarian cancer cells treated with carboplatin and explored the mechanism underlying ovarian cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Through SA-β-galactosidase staining in an ovarian cancer cell line, Li et al showed that overexpression of EGFR inhibited the carboplatin-induced senescence-like phenotype. At the same time, EGFR knockdown may contribute to the carboplatin-induced senescence-like phenotype [54]. EGFR knockdown also induced senescence in gallbladder cancer cells GBC-SD and NOZ.…”
Section: Tumor Microenvironmentmentioning
confidence: 94%
“…Through SA-β-galactosidase staining in an ovarian cancer cell line, Li et al showed that overexpression of EGFR inhibited the carboplatin-induced senescence-like phenotype. At the same time, EGFR knockdown may contribute to the carboplatin-induced senescence-like phenotype [54]. EGFR knockdown also induced senescence in gallbladder cancer cells GBC-SD and NOZ.…”
Section: Tumor Microenvironmentmentioning
confidence: 94%
“…On the other hand, it has also been shown to potentiate tumor heterogeneity, resistance [6], and relapse [7]. For instance, TIS in ovarian cancer cells leads to their transient dormancy, which can be reversed to re-initiate proliferation [8,9]. TIS-associated cytokine secretion (as part of the broader phenomenon of senescence-associated secretory phenotype or SASP) may accentuate infiltration by tumor-associated macrophages (TAMs) in primary tumors leading to greater invasion and metastasis [10][11][12].…”
Section: Introductionmentioning
confidence: 99%